Testing The Ability of Smartphones to Locate Devices With A Bluetooth Interface - Artur ARCIUCH (Communications of International Proceedings, 2021)
Systems for indoor location of objects, as the GPS signal is not available inside buildings, utilise, among others, devices with Bluetooth and WiFi interface. To determine the location of objects (devices), measurements using the value of the signal power (WiFi, Bluetooth, etc.) between them are made - as the distance increases, the value of the signal power decreases. Specialised equipment in the form of access points for WiFi and Bluetooth-enabled devices is generally used for localisation, and the distance is determined by a value of RSSI parameter. The paper presents the results of distance measurements made with commonly used computer equipment: a laptop computer and smartphones. The experiments show that mobile devices equipped with Bluetooth modules, such as smartphones, tablets and other laptops, can be used to determine the coarse location of objects in a building.
Keywords: Bluetooth; RSSI; Localization